"Exchange rate risk" within the European Monetary Union? Analyzing the exchange rate exposure of German firm - Oliver Entrop; Matthias F. Merkel (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2018)
In this paper we show that inflation differentials among the countries in the European Monetary Union (EMU) are an economically significant risk to German firms, which make up the largest economy in the EMU. This risk can be interpreted as real "exchange rate exposure" resulting from trade within the euro area. Actually, we find that this EMU exposure is nearly as high as the standard exchange rate exposure caused by trade with non-EMU countries. Moreover, our analysis shows that many of the conventional factors that drive firm-specific exchange rate risk, such as size, debt ratio, asset turnover and foreign business activity, also determine EMU exposure in an economically meaningful way. However, EMU exposure challenges firms' risk management, particularly as it cannot be reduced by standard financial hedging instruments, such as currency derivatives.
Keywords: F23; F31; G15; 650; currency risk; inflation differentials; single-currency area